2018
DOI: 10.1111/nyas.13980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phytochemicals on thyroid function and their possible role in thyroid disease

Abstract: About 1 of 10 women, particularly those older than 60 years of age, shows some degree of thyroid hormone deficiency. Thyroid diseases are generally characterized by perturbations of thyroid signaling homeostasis. The most common examples of thyroid diseases include hypothyroidism, hyperthyroidism, and several types of thyroid cancers. Phytochemicals have been shown to have either beneficial or detrimental effects on thyroid function. Some flavonoids have been reported to affect the expression and the activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…Ferulic acid might act as an anticancer drug by inhibiting autophagy, inducing cell cycle arrest [34], and inducing apoptosis [35]. Phytochemicals had been shown to have either beneficial or detrimental effects on thyroid function [56]. However, the role of the above substances except for hesperidin in thyroid diseases has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Ferulic acid might act as an anticancer drug by inhibiting autophagy, inducing cell cycle arrest [34], and inducing apoptosis [35]. Phytochemicals had been shown to have either beneficial or detrimental effects on thyroid function [56]. However, the role of the above substances except for hesperidin in thyroid diseases has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that some chemicals which alter the genes involved in the HPT axis homeostasis may be associated with an increased incidence of thyroid dysfunction, such as hypothyroidism, hyperthyroidism and cancer (69)(70)(71)(72). Among these, halogenated phenols, tributyltin, polychlorinated biphenyls and surfactants act on the hypothalamus and pituitary, while perchlorate, nitrates, thiocyanates, parabens and pesticides act on the thyroid gland itself (73,74).…”
Section: Glyphosate Toxicity In Hpt Axismentioning
confidence: 99%
“…[35] It should be noted that in vitro studies have demonstrated that quercetin and other flavonoids interfere with thyroid hormone synthesis at multiple steps in the synthetic pathway. [36][37][38][39] The use of quercetin has rarely been associated with hypothyroidism. The clinical impact of this association may be limited to those individuals with pre-existent thyroid disease or those with sub-clinical thyroidism.…”
Section: Prophylaxismentioning
confidence: 99%